Educação empreendedora: (des)socialização e subsunção do trabalho ao capital - Almeida, Luiz Carlos Tavares de (2023)
Based on the assumption that education has an "organic" relationship with the social structure to which it belongs, since it is part of this totality and is engendered by it, the general objective of this thesis is to analyze the process of entrepreneurship in public education and its relationship to the promotion of entrepreneurship in the school curriculum, with emphasis on the process of restructuring the curriculum of public high school education in the state of Sergipe. For this, its development was based on the analysis and questioning of the radical interference of the business sectors in the elaboration and conduction of educational policy, especially when editing, inside the educational processes, the unrestricted imposition of an ideal of human formation tending to conformism and the adaptation of the subjects to the precariousness of the current work relations. Imbued with an instrumental ideological character, the High School Reform was imposed as a natural process of modernization, treated as a measure alien to power relations and without historicity. In these terms, the nodal point of the so-called "entrepreneurial education", advocated by the high school reform and the new BNCC, is to affirm individualism as an ethical-political principle to legitimize the notion of meritocracy, establishing links between employability, entrepreneurialism, the minimal state model, flexible work, and the pattern of accumulation in neoliberal terms. To account for these multiple defining determinations of the concrete real, this research was structured on three fundamental pillars - State, capital, and labor. According to Mészáros (2015), these pillars underpin the entire system of capital; they are responsible for feeding, from structural contradictions, a vicious circle of corrective practices and historically unsustainable social cohesion. In terms of method, this thesis is based on historical-dialectical materialism, adopted as a method for interpreting reality, worldview, and praxis, and on the Critical-Historical theory, an analytical reference without which we would not have advanced in the understanding and questioning of the instrumentalizing dynamics of the educational work. The fieldwork was designed and articulated with the need to capture the concrete dynamics objectified by the research subjects in mind. This entire scenario has pointed to an ongoing process - the deepening of the educational duality, the instrumentalization of the formative processes and the improvement of an educational culture (strongly influenced by the "learn to learn" pedagogies) committed to the development of individualistic agendas and the adaptation of work (via the transfer of instrumental competencies and skills) to the precariousness of the informal market.